Dopamine Optimizes Venous Return During Cardiopulmonary Bypass and Reduces the Need for Postoperative Blood Transfusion. Issue 8 (November 2019) - Moscarelli, Marco; Condello, Ignazio; Fattouch, Khalil; Punjabi, Prakash; Ajello, Valentina; Solimando, Carlo; Fiore, Flavio; Angelini, Gianni; Speziale, Giuseppe
Abstract : Venodilation occurs shortly after the institution of cardiopulmonary bypass (CPB), necessitating fluid or vasoconstrictor administration to maintain adequate oxygen delivery. The vasoconstrictor effects of dopamine are not well studied in this context. Therefore, we conducted a single-center, double-blind case–control study to determine the role and utility of dopamine as a vasoconstrictor during CPB. The study included 60 adults who were scheduled for isolated elective/urgent coronary artery bypass grafting. Patients in group A (n = 30) received a dopamine bolus (2 mg) 20 min after cross-clamping, whereas patients in group B (n = 30) did not receive any intervention at a specific time point. Both groups received standard care as needed (fluid replacement or norepinephrine bolus). Venous return was measured directly in the reservoir and indirectly by Doppler measurement at the level of the inferior vena cava with transesophageal echocardiography. Both open and closed circuits were used for CPB. A single dopamine bolus (2 mg) increased volume in the venous reservoir in group A. Group A patients also received significantly fewer units of red blood cells in the intensive care unit (ICU) than did patients in group B. There were no significant between-group differences in postoperative bleeding, mechanical ventilation, or length of stay in the ICU. These findings suggest that use of a dopamine bolus can increase venous return and reduce the need for fluid replacement during and after CPB in patients undergoing coronary artery bypass grafting. Abstract : Supplemental Digital Content is available in the text.